Divorce and remarriage among Muslims in India - Ahmad, Imtiaz.( ed.) (New Delhi, 2003)
Divorce is usually studied in terms of two distinct perspectives.One focuses on the procedure laid down for giving the seal of finalauthority to a divorce. The other explores the processes that areset in motion once the stability of a marriage is threatened. Thelatter perspective does not see divorce in isolation but treats itin the wider context of social structure. When divorce in Muslimcommunities is discussed, the tendency quite often is to placetheology and law at the centre. This book recognizes that divorcein Muslim communities entails substantial theological and legaldimensions, but takes as its point of departure the view that it isonly by placing divorce in the social and cultural context thatmeaningful conclusions can be arrived at. It examines, in the lightof empirical evidence, the incidence of divorce and separation, thesocial and other causes due to which divorce and separation takesplace, and the position of divorced women in society as well astheir prospects of remarriage. In the process substantialmethodological and theoretical questions relevant to the study ofdivorce as a social phenomenon are raised. The book has animmediate practical aim as well. Muslim law of divorce,particularly the provision of triple divorce, which vests aunilateral right in the husband to pronounce a summary divorce uponhis wife, has been the subject of considerable controversy.Essentially, the papers brought together in this book aresociological analyses of divorce and remarriage among Muslims inIndia and the data thrown up as part of these analyses should clearsome points in the controversy.
Keywords: Muslims